Teacher Competence in Character Education Through Technology-Enhanced Innovative Learning of Integrated Social Sciences. - Mukhlisoh, Mukhlisoh (EduTech Journal, 2024)
This study aims to investigate the competence of Madrasah Ibtidaiyah (MI) teachers in character education through innovative learning in Integrated Social Studies subjects. The research uses a quantitative survey method to find the relationship between variables about self-confidence and behavior. The results of the study revealed that the percentage of teacher pedagogical competence was 52%, personality competence was 60%, social competence was 75%, and professional competence was 67%. There is a positive influence of teacher competence simultaneously through innovative integrated social studies learning on the character education of students by 70.5%. The conclusion obtained is that the competence of integrated social studies subject teachers needs to be improved to support the character education of students through innovative learning during the Covid 19 pandemic. It is hoped that teachers will have the ability to support and motivate students to study better and obtain satisfactory achievements even amid the pandemic situation and the limitations of face-to-face learning. The expected implication is that the government supports and facilitates training and funding for the welfare of MI teachers. So that MI teachers can be more advanced in their work and support national education goals.